2010
DOI: 10.1007/s10753-010-9254-8
|View full text |Cite
|
Sign up to set email alerts
|

Baicalin Inhibits TLR2/4 Signaling Pathway in Rat Brain Following Permanent Cerebral Ischemia

Abstract: Recent work from our laboratory demonstrated that baicalin attenuates inflammatory reaction and cerebral ischemia injury in rats. Toll-like receptor 2 and 4 (TLR2/4) and the downstream nuclear factor-kappa B (NF-κB) signaling pathway, which mediate the inflammatory reaction, are involved in the pathophysiological processes of cerebral ischemia. In this study, we investigated whether baicalin inhibits TLR2/4 signaling pathway in a rat model of permanent focal cerebral ischemia. Adult Sprague-Dawley rats underwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
55
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 81 publications
(58 citation statements)
references
References 28 publications
2
55
0
Order By: Relevance
“…The experimental results also showed that the neuroprotective and antiinflammatory role of baicalin in ischemic stroke might be associated with the inhibition of toll-like receptor 2/4 (TLR2/4) signaling pathway [12]. Similarly, baicalin is also considered to protect brain from cerebral ischemiareperfusion by down-regulating the expression of nucleotide-binding oligomerization domain protein 2 (NOD2) and TNF-a [18].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The experimental results also showed that the neuroprotective and antiinflammatory role of baicalin in ischemic stroke might be associated with the inhibition of toll-like receptor 2/4 (TLR2/4) signaling pathway [12]. Similarly, baicalin is also considered to protect brain from cerebral ischemiareperfusion by down-regulating the expression of nucleotide-binding oligomerization domain protein 2 (NOD2) and TNF-a [18].…”
Section: Discussionmentioning
confidence: 97%
“…Recent studies from our laboratory have shown that baicalin reduces ischemic brain damage by inhibiting inflammatory reaction and neuronal apoptosis [11,12]. In the present study, we, for the first time, explored whether baicalin reduces ischemia-induced brain edema and BBB permeability, and further investigated the effect of baicalin on the expression of MMP-9 and occludin.…”
Section: Introductionmentioning
confidence: 88%
“…1), a flavonoid isolated from Scutellaria baicalensis is known to have multiple biological functions including anti-oxidant, anti-tumor, antiischemic, and anti-inflammatory properties (Jung et al 2008;Li-Weber 2009). The inhibitory effects of baicalin on inflammation are associated with the inhibition of NF-jB activation, as has been shown in various acute and chronic inflammation models, including severe acute pancreatitis (Xiping et al 2010), air embolism-induced acute lung injury ), cerebral ischemia (Tu et al 2010), and chronic obstructive pulmonary disease (Lixuan et al 2010). Further, in a previous study, we demonstrated that baicalin treatment suppresses the activation of NF-jB and related inflammatory genes in aging kidneys (Kim et al 2006).…”
mentioning
confidence: 99%
“…Baicalin, an active ingredient originally isolated from the root of a Chinese herb Huangqin (S. baicalensis Georgi), has been frequently used as an antiinflammatory drug in TCM practice [12][13][14][15]. Our findings suggest that the anti-inflammatory properties of baicalin may result from the inhibition of IL-6, IL-8, and TNF-α expression via preventing signaling NF-κB pathway in HBE16 airway epithelial cells.…”
Section: Discussionmentioning
confidence: 69%